Electronically tunable voltage-mode Elliptic third-order ladder low-pass filter using simple OTA - Tiamsuphat, Aphinat; Prommee, Pipat (My University, 2014)
This paper presents Elliptic third-order voltage-mode ladder low-pass filter based on CMOS technology, Using OTA. Third-order low pass filter is designed based on RLC Elliptic Ladder low-pass filter prototype. The proposed filter contains lossless integrators and voltage gains. The frequency responses of low-pass filter can be electronically tuned between around 3kHz and 2MHz by adjusting bias current from 0.01μA to 10μA with 1mW of dynamic power consumption along the tuning range. The circuit used ±1.5V power supply and used of ground capacitors which suit to integrated circuit. THD of low-pass filter can be obtained less than 0.7% along the operating frequencies. PSPICE simulation results are carried out to confirm the theory by using TSMC 0.18μm CMOS technology.
Keywords: Elliptic; Low-pass; OTA-C; Voltage-mode